Forecasting the volume of agricultural machinery write-off: a methodological approach (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The study is devoted to a methodological approach to forecasting the volume of agricultural machinery write-off. The relevance of the problem of utilization of technical means of the agro-industrial complex in the context of environmental, economic and social challenges is considered. The purpose of the research is to develop a methodology for forecasting the annual volume of agricultural machinery written-off, taking into account the dynamics of changes in the technical fleet, the intensity of renewal and average specific indicators. The work analyzes the dynamics of changes in the agricultural machinery fleet by type, quantity and brand. The intensity of renewal of the technical fleet is estimated and the average terms of writing-off of various types of agricultural machinery are studied. Based on the data obtained, a model for forecasting the amount of machinery to be written-off is developed. The results of the study will allow developing effective measures to reduce costs for utilization and increase the efficiency of using secondary resources. The obtained data can be used to form regional and national programs for the disposal of agricultural machinery, as well as to develop business plans for enterprises engaged in disposal and processing.
Keywords: forecast; write-off; methodology